"Slum Clearance" in 1890s Wellington - Cox, Elizabeth (Architectural History Aotearoa, 2023)
In 1892, a remarkable map of Wellington was completed. Stretching from Thorndon in the north to Berhampore to the south, and taking in the teeming inner-city areas of Te Aro and Newtown, the remnants of Māori kāinga, the town belt, the Basin Reserve, the prison, "lunatic asylum" and hospital, reclamations and every street in between. The map, drawn by engineer and surveyor Thomas Ward, is actually 103 maps, drawn on A1 sheets. On the map, the exact footprint of every single building in Wellington is recorded every commercial building and house, every garden shed and outdoor toilets. Bay windows and verandahs are carefully drawn. Data is recorded for every building, including how many rooms it contains, what the roof and walls are made of and how many storeys it has. Legal titles are exactly mapped, as are the city's streams and even the street lights. Once complete, one full pristine set of the maps was set aside and preserved intact. Another set of the maps was updated regularly, for approximately the next ten years. For that decade, we can follow every change in the city, down to the smallest detail such as the replacement of slate rooves with corrugated iron, but also bigger-scale work such as the reconfiguration of whole streets. The Thomas Ward map is a touchstone for the history of our city. It is used every day by Wellington's archaeologists and historians. Wellington City Council provides the map online as an digital overlay over modern satellite images of the city, allowing us to compare the city of 1892 to the city of today. A well-known feature of the history of Wellington in the 1890s was the outbreak of typhoid and other diseases in the inner-city, a result of overcrowding and lack of clean water. To combat this, a number of "slum clearances" were ordered by the city council, resulting in whole streets of working-class houses being demolished. This paper, a part of a much larger project, will examine some of the stories shown in the two sets of maps, with a particular focus of the changed landscape of the inner-city brought about by this "slum clearance" work of the 1890s.